2020
DOI: 10.1101/2020.06.18.146720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GLP-1R agonist NLY01 reduces retinal inflammation, astrocyte reactivity, and retinal ganglion cell death secondary to ocular hypertension

Abstract: Glaucoma is the leading cause of irreversible blindness worldwide and is characterized by the death of retinal ganglion cells. Reduction of intraocular pressure (IOP) is the only therapeutic mechanism available to slow disease progression. However, glaucoma can continue to progress despite normalization of IOP. New treatments are needed to reduce vision loss and improve outcomes for patients who have exhausted existing therapeutic avenues. Recent studies have implicated neuroinflammation in the pathogenesis of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In a recent study by our group, we showed that treatment with NLY01 reduced production of all three pro-inflammatory cytokines by microglia/macrophages in this mouse model of glaucoma (Sterling et al, 2020a). Further, NLY01 treatment prevented A1 astrocyte transformation and rescued retinal ganglia cells in these animals (Sterling et al, 2020a). GLP-1R agonists reduce blood-retina barrier (BRB) permeability by down-regulating pro-inflammatory cytokines and protect tight junctions in rodent models of diabetes (Simo & Hernandez, 2017).…”
Section: Glp-1 In Neurodegenerative Diseases and Glaucomamentioning
confidence: 78%
See 4 more Smart Citations
“…In a recent study by our group, we showed that treatment with NLY01 reduced production of all three pro-inflammatory cytokines by microglia/macrophages in this mouse model of glaucoma (Sterling et al, 2020a). Further, NLY01 treatment prevented A1 astrocyte transformation and rescued retinal ganglia cells in these animals (Sterling et al, 2020a). GLP-1R agonists reduce blood-retina barrier (BRB) permeability by down-regulating pro-inflammatory cytokines and protect tight junctions in rodent models of diabetes (Simo & Hernandez, 2017).…”
Section: Glp-1 In Neurodegenerative Diseases and Glaucomamentioning
confidence: 78%
“…The accumulating evidence is suggestive of a complex putative multicellular anti-inflammatory and neuroprotective action of GLP-1R agonists on neurons, astrocytes and microglia. GLP-1, glucagon-like peptide-1; RGC, retinal ganglion cell rescued retinal ganglia cells in a microbead-induced mouse model of acute, hypertensive glaucoma (Guttenplan et al, 2020;Sterling et al, 2020a). In a recent study by our group, we showed that treatment with NLY01 reduced production of all three pro-inflammatory cytokines by microglia/macrophages in this mouse model of glaucoma (Sterling et al, 2020a).…”
Section: Glp-1 In Neurodegenerative Diseases and Glaucomamentioning
confidence: 82%
See 3 more Smart Citations